Enterprise Architecture Blending Cycle - Septian Rheno Widianto; Rakhmadi Rahman; Lia Kamila Kulsum; M Yahtadi (Institute of Computer Science (IOCS), 2020)
The purpose of implementing Enterprise Architecture (EA) is to create alignment between the enterprise architecture and the strategic plans of institutions and business functions, allocation of institutional resources, and selection of information technology tailored to the institutional business needs. To develop the application of EA, an EA methodology is needed with a Blended Methodology approach from several EA (Enterprise Architecture Planning (EAP) methodologies, The Open Group Architecture Framework - Architecture Development Method (TOGAF-ADM), Oracle Architecture Development Process (OADP), Enterprise Unified Process. (EUP). By knowing the relationship between several EA methodologies, a new methodology can be generated that can help develop the EA implementation of an institution to achieve its strategic objectives.